Giardia spp in dogs and children in rural communities of three districts of Puno, Peru - Pablo J., Olguita (2012)
The aim of this study was to determine the prevalence of Giardia spp in dogs and children in three rural communities in Puno, Peru. Fecal samples were collected (n = 130) from both children and apparently healthy dogs of both sexes and different ages. The Sheather and spontaneous sedimentation technique were used for the diagnosis of Giardia. A sample was considered positive if at least one positive result in any of the two techniques was found. The overall prevalence was 14.6 ± 6.1 and 28.5 ± 7.8% in dogs and children respectively. Sex, age, and location in both children and dogs were not statistically associated with the presence of the parasite. The results of prevalence of Giardia in dogs and children suggest a possible zoonotic risk.